LSST survey strategy in the galactic plane and magellanic clouds - Street, Rachel; Li, X.; Khakpash, S.; Bellm, E.; Girardi, L.; Jones, L.; Abrams, N. S.; Tsapras, Yiannis; Hundertmark, Markus; Bachelet, E.; Gandhi, P.; Szkody, P.; et al. (The astrophysical journal. Supplement series, 2023)
Galactic science encompasses a wide range of subjects in the study of the Milky Way and Magellanic Clouds, from young stellar objects to X-ray binaries. Mapping these populations, and exploring transient phenomena within them, are among the primary science goals of the Vera C. Rubin Observatory’s Legacy Survey of Space and Time. While early versions of the survey strategy dedicated relatively few visits to the Galactic Plane region, more recent strategies under consideration envision a higher cadence within selected regions of high scientific interest. The range of galactic science presents a challenge in evaluating which strategies deliver the highest scientific returns. Here we present metrics designed to evaluate Rubin survey strategy simulations, based on the cadence of observations they deliver within regions of interest to different topics in galactic science, using variability categories defined by timescale. We also compare the fractions of exposures obtained in each filter with those recommended for the different science goals. We find that the baseline_v2.x simulations deliver observations of the high-priority regions at sufficiently high cadence to reliably detect variability on timescales >10 days or more. Follow-up observations may be necessary to properly characterize variability, especially transients, on shorter timescales. Combining the regions of interest for all the science cases considered, we identify those areas of the Galactic Plane and Magellanic Clouds of highest priority. We recommend that these refined survey footprints be used in future simulations to explore rolling cadence scenarios, and to optimize the sequence of observations in different bandpasses.
Gesehen am 07.08.2023